Substance Abuse in the Czech Population: Reflections on threats, their value context and possibilities of social prevention - Olecká, Ivana (Univerzita Palackého v Olomouci, 2022)
Kniha mapuje reflexi sociálních a zdravotních ohrožení abúzem návykových látek v populaci České republiky.
Keywords: Sociologie